2001
DOI: 10.1148/radiology.219.1.r01ap28213
|View full text |Cite
|
Sign up to set email alerts
|

Primary versus Secondary Ovarian Malignancy: Imaging Findings of Adnexal Masses in the Radiology Diagnostic Oncology Group Study

Abstract: For malignant ovarian masses, multilocularity at MR imaging or US favors the diagnosis of primary ovarian malignancy rather than secondary neoplasm, but it is difficult to accurately distinguish between primary and secondary ovarian malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
2
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 20 publications
1
87
2
6
Order By: Relevance
“…When increased FDG uptake is seen simultaneously in the ovary and other organs, such as the stomach or colon, on PET/CT images, MOTs are the most likely culprit, as opposed to primary ovarian tumors. Additionally, because the imaging findings of MOTs according to primary tumor site are known (Brown et al 2001;Choi et al 2005;Koyama et al 2007), use of the CT portion of PET/CT combined with FDG uptake analysis can assist differentiation of MOTs from primary ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…When increased FDG uptake is seen simultaneously in the ovary and other organs, such as the stomach or colon, on PET/CT images, MOTs are the most likely culprit, as opposed to primary ovarian tumors. Additionally, because the imaging findings of MOTs according to primary tumor site are known (Brown et al 2001;Choi et al 2005;Koyama et al 2007), use of the CT portion of PET/CT combined with FDG uptake analysis can assist differentiation of MOTs from primary ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In general, imaging reports have suggested that most metastatic neoplasms are predominantly solid or a mixture of cystic and solid areas. However, in a comprehensive study, Brown et al (10) reported neither predominantly solid appearance nor bilateral ovarian involvement to be significantly different between primary and secondary neoplasms. The imaging characteristics depend on the primary tumor.…”
Section: Historymentioning
confidence: 98%
“…For adnexal masses that appear complex or possibly malignant on US, magnetic resonance (MR) imaging adds significant further information, with a reported accuracy as high as 91% [4,[6][7][8]. In this specific setting, some criteria are highly suggestive for benign ovarian lesions (e.g., fatty components, shading on T2-weighted images) [9,10], whereas vegetations and solid portions within cystic masses have been shown to be the best predictors of malignancy [7,11]. Using these different criteria, a preliminary diagnosis can be made before surgery.…”
Section: Introductionmentioning
confidence: 99%